2020
DOI: 10.1101/2020.02.13.936252
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

STAT1-dependent tolerance of intestinal viral infection

Abstract: 1Recent evidence indicates that viral components of the microbiota can contribute to intestinal 2 homeostasis and protection from local inflammatory or infectious insults. However, host-derived 3 mechanisms that maintain tolerance to the virome remain largely unknown. Here, we use 4 colonization with the model commensal murine norovirus (MNV CR6) to interrogate host-5 directed mechanisms of viral tolerance, and show that STAT1 is a central coordinator of 6 tolerance following CR6 colonization. STAT1 restricts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Several other studies have demonstrated the impaired immune responses and augmented outcomes followed by bacterial and viral respiratory infections in the absence of gut microbiota 84,104,117 . Gut microbiota–derived signals have been shown to activate signal transducer and activator of transcription‐1 (STAT1), which is critically involved in antiviral gene expression 84,118 . Further, probiotic microorganisms such as Lactobacillus and Bifidobacterium have significantly reduced the occurrence of respiratory infections followed by antibiotic‐induced changes in gut microbiota composition.…”
Section: Gut–lung Axis Rtis and Probiotic Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other studies have demonstrated the impaired immune responses and augmented outcomes followed by bacterial and viral respiratory infections in the absence of gut microbiota 84,104,117 . Gut microbiota–derived signals have been shown to activate signal transducer and activator of transcription‐1 (STAT1), which is critically involved in antiviral gene expression 84,118 . Further, probiotic microorganisms such as Lactobacillus and Bifidobacterium have significantly reduced the occurrence of respiratory infections followed by antibiotic‐induced changes in gut microbiota composition.…”
Section: Gut–lung Axis Rtis and Probiotic Microorganismsmentioning
confidence: 99%
“…84,104,117 Gut microbiota-derived signals have been shown to activate signal transducer and activator of transcription-1 (STAT1), which is critically involved in antiviral gene expression. 84,118 Further, probiotic microorganisms such as Lactobacillus and Bifidobacterium have significantly reduced the occurrence of respiratory infections followed by antibiotic-induced changes in gut microbiota composition. Probiotics can induce Treg cells, which are involved in the downregulation of allergic responses.…”
Section: Gut-lung Axis Rtis and Probiotic Microorganismsmentioning
confidence: 99%
“…The most relevant pathways encoded by them were transmembrane transport and IL4 and IL13 signaling (Supplementary Table S6). For SARS-CoV-2,the top 20 proteins were ANKRD49, GGA1, NAGLU, SORL1, TRIM59, GAS2L3, PTPRH, DRD1, RHOV, VPS35L, ZNF581, SAMD9, TBC1D3, DUOXA1, IL18, LPAR2, OPN5, GSTM3 and SPATA12 responsible for interleukin signaling pathway of the immune system (Supplementary Table S7; Supplementary Table S8) and interestingly most of them reported to be involved induced during different kind of viral infection having some role on host defense response and inflammation ( Menner et al, 2015 ; Filyk et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The proposed network-based dietary supplements/anti-inflammatory compounds discovery depends on the hypothesis that the important hub proteins that functionally govern viral infection localized in the corresponding subnetwork would be the target for compounds or dietary supplements ( Filyk et al, 2020 ). Using Comparative Toxicogenomics Database (CTD), we identified the possible dietary supplements/ant-inflammatory compounds which known to have possible interaction with the hub proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Gut bacteria regulate the activation of the interferons (IFNs) signaling, which is crucial for response against the majority of viruses, and inflammasome activity, an innate signaling pathway that is involved in defense against a subset of viruses [42]. In the steady-state, gut microbial-derived signals regulate low-level signal transducer and activator of transcription-1 (STAT1) activation [42], which is critical for IFNs signaling, and is involved in antiviral defense genes induction prior to infection and immune-mediated resistance to viral infection [42,43]. Figure 1 illustrates the role of gut microbiota in the prevention of viral respiratory infections.…”
Section: Gut-lung Axis and Viral Respiratory Infectionsmentioning
confidence: 99%